1997
DOI: 10.1063/1.118620
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in oxygen precipitation in silicon after high temperature rapid thermal annealing

Abstract: Spatial variations of oxygen precipitation have been studied in silicon wafers submitted to rapid thermal annealing (RTA) in nitrogen ambients at a temperature above 1150 °C prior to a two-step precipitation treatment. The samples submitted to high temperature preannealing show a consistent enhancement of oxygen precipitation, which is dependent on the RTA time and temperature. Oxygen precipitate density measurements show that oxygen precipitation is not homogeneous inside the wafer, but peaks near the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Anneals were accomplished in an ultra-high purity nitrogen ambient (99.999 % purity, oxygen and water vapor concentration in the gas are less than one part per million parts in volume) in both types of furnaces. Although, a nitrogen rich ambient has been shown to lead to greater density of structural defects than an argon rich ambient [16,17], the former was chosen to facilitate a better comparison to the existing literature.…”
Section: Methodsmentioning
confidence: 99%
“…Anneals were accomplished in an ultra-high purity nitrogen ambient (99.999 % purity, oxygen and water vapor concentration in the gas are less than one part per million parts in volume) in both types of furnaces. Although, a nitrogen rich ambient has been shown to lead to greater density of structural defects than an argon rich ambient [16,17], the former was chosen to facilitate a better comparison to the existing literature.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, RTA technology was employed to build a vacancy concentration depth profile in silicon wafer, which is another approach for the creation of DZ. Followed by low-high two-step annealing, the oxygen precipitation behavior is well controlled by vacancy profile rather than oxygen concentration profile, thus DZ is believed to be independent of the initial oxygen concentration, thermal history and so on [22,23].…”
Section: Specimensmentioning
confidence: 97%
“…During the RTP in N 2 , it is believed that a nitride film was formed on the wafer surface, which injected vacancies into the wafer bulk. Meanwhile, an amount of nitrogen atoms could also diffuse into the wafer bulk to react with the vacancies and oxygen atoms to generate N-O-V complexes [7,10], which would retard the out-diffusion…”
mentioning
confidence: 99%
“…Over the years, a novel IG process based on rapid thermal processing (RTP), has been well developed, in which the behaviour of oxygen precipitation is controlled by vacancy profile [5,6]. Furthermore, it has been reported that the protective ambient of RTP affect the formation of DZ and oxygen precipitation due to the different intrinsic point defect profiles [7,8]. For instance, additional vacancies can be injected into silicon wafers during RTP in N 2 ambient [6,9]; while, the self-interstitials would be injected into silicon wafers due to the RTP in O 2 ambient [8].…”
mentioning
confidence: 99%